2023
DOI: 10.12688/f1000research.136653.1
|View full text |Cite
|
Sign up to set email alerts
|

Preventive efficacy of silver diamine fluoride and MI Varnish on molars affected by molar incisor hypomineralization in children: A randomized controlled trial

Zuhair Al-Nerabieah,
Muaaz AlKhouli,
Mayssoon Dashash

Abstract: Background: This randomized controlled trial aimed to compare the efficacy of silver diamine fluoride (SDF) and MI Varnish in preventing caries development, enamel breakdown, and sensitivity on molars affected by molar incisor hypomineralization (MIH) in children. Methods: A total of 100 children aged 6 to 9 years were enrolled in the study with two contralateral permanent molars mildly affected by MIH. Affected molars were randomly and equally assigned to receive either SDF or MI Varnish treatment. The interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Each child had two contralateral permanent 1 st molars affected with mild MIH. 24 The distribution of the molars involved in the study is summarized in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each child had two contralateral permanent 1 st molars affected with mild MIH. 24 The distribution of the molars involved in the study is summarized in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the study was designed and reported according to the Consolidated Standards of Reporting Trials (CONSORT) statement criteria to ensure rigorous and transparent reporting of the study methodology and results. 20…”
Section: Ethical Considerationsmentioning
confidence: 99%
“…It should be noted that the sample population for this study had previously participated in a randomized controlled trial (RCT) comparing the preventive efficacy of SDF and MI Varnish on molars affected by MIH in children 9 . A total of 100 participants met the eligibility criteria and consented to participate in the study.…”
Section: Methodsmentioning
confidence: 99%
“…One such innovation that has garnered considerable attention in the pediatric dentistry community is the utilization of silver diamine fluoride (SDF) 8 , 9 . This minimally invasive and cost-effective treatment has emerged as a beacon of hope for dental practitioners faced with the task of managing MIH 10 .…”
Section: Introductionmentioning
confidence: 99%